2013
DOI: 10.1371/journal.pone.0076272
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in Healthcare Workers and Infection Control Measures at Primary Healthcare Facilities in South Africa

Abstract: BackgroundChallenges exist regarding TB infection control and TB in hospital-based healthcare workers in South Africa. However, few studies report on TB in non-hospital based healthcare workers such as primary or community healthcare workers. Our objectives were to investigate the implementation of TB infection control measures at primary healthcare facilities, the smear positive TB incidence rate amongst primary healthcare workers and the association between TB infection control measures and all types of TB i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(107 citation statements)
references
References 19 publications
5
100
1
1
Order By: Relevance
“…The lack of implementation and scale up of these preventative measures, with an emphasis on rapidly diagnosing and treating unsuspected TB, are primarily responsible for nosocomial TB transmission 10,34,35 . In HBCs such as South Africa, poor building design, overcrowding, lack of knowledge and training regarding facility-based IC plans and guidelines, and poor managerial involvement in the design and implementation of local TB-IC policy have been noted as barriers to the implementation of such measures 36,37 .…”
Section: Challengesmentioning
confidence: 99%
“…The lack of implementation and scale up of these preventative measures, with an emphasis on rapidly diagnosing and treating unsuspected TB, are primarily responsible for nosocomial TB transmission 10,34,35 . In HBCs such as South Africa, poor building design, overcrowding, lack of knowledge and training regarding facility-based IC plans and guidelines, and poor managerial involvement in the design and implementation of local TB-IC policy have been noted as barriers to the implementation of such measures 36,37 .…”
Section: Challengesmentioning
confidence: 99%
“…29,30 In some studies smear positivity was defined as at least 1 25,27,28,30,35,41,42 or at least 2 [22][23][24]34 positive smears, whereas others did not provide any definition. 10,21,26,[31][32][33][36][37][38][39][40] A study from South Africa stratified rates of reported pre-treatment loss to followup by smear status (smear-positive or smear-negative but culture-positive), 23 whereas another study, also from South Africa, reported on pre-treatment loss to follow-up in tuberculosis patients whose diagnosis was established clinically and/ or bacteriologically. 29 …”
Section: Study Characteristicsmentioning
confidence: 99%
“…41 The recruitment periods ranged from 3 months 24,34,36 to 90 months. 30 Only 9 studies [22][23][24][25]27,29,31,36,37 applied a cut-off for time since diagnosis -ranging from 1 month to 3 months -to define pretreatment loss to follow-up.…”
Section: Quality Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…1,3,11 Personal testimonials of HCW who contracted occupational TB were shared to counter the misconception that only immune-compromised people develop TB. Students could relate to their fellow HCW experiences of the devastating effects of occupational TB.…”
Section: Application In Interventionmentioning
confidence: 99%